Effects of probiotics and enzymes on growth performance and haematobiochemical parameters in broilers (Journal of the Bangladesh Agricultural University, 2014)
An study was conducted on "Cobb-500" broiler chicks to evaluate the effects of probiotics and enzymes supplementation on growth performance, haematological and biochemical parameters. A total of 20, fourteen days old broiler chicks were divided randomly into four groups using five broiler chicks in each group. Group A was designated as control group was given only normal broiler ration and rest of the groups were fed probiotics and enzymes, [Group B (probiotic Microguard® @ 1 gm/L), Group C (enzymes preparation Acmezyme* 1 gm/L), Group D (Microguard* g 1 gm/L and Acmezyme @ 1 gm/L)] with drinking water respectively from 1St to 21st day of study. It was observed that probiotics and enzymes supplementation enhanced the body growth rate. At the final day of experiment the body weight was significantly increased (P